RESPON PEMBERIAN HORMON TUMBUH DAN MIKORIZA TERHADAP PERTUMBUHAN STEK RAMIN (GONYSTYLUS BANCANUS (MIQ.) KURZ) - Wikan Utami, Ning (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2011)
This study was conducted to determine the effect of growth hormones and mycorhyza application on the growth of ramin cuttings. A Completely Randomized Design with 5 replicates was used in this study. The experiment consisted of two stages i.e hormon treatments (control, Rapid root, Root Up, IBA 250 mg/l, IBA 500 mg/l, IBA 1000 mg/l), Fusarium and mycorhyza applications. The result showed that the highest number of root was obtained from Root Up (12,83 cm), while the lowest was from Fusarium treatments (4,67 cm). IBA 250 mg/l enhanced the number of roots and the length of root significantly but not stimulate the development of new leaf. While mycorhyza application improving the growth of the new leaf and the root development of ramin.